The diagnostic performance of the one-step nucleic acid amplification assay for the detection of sentinel lymph node metastases in cytokeratin 19-positive breast cancer: a PRISMA-compliant meta-analysis - Liu, Meirong; Wang, Weihua; Wang, Yufang (Frontiers in Medicine, 2024)
Background The status of the sentinel lymph nodes (SLNs) is an important prognostic factor for many different types of cancer. The one-step nucleic acid amplification (OSNA) assay has emerged as a rapid intraoperative molecular diagnostic tool for LN metastasis detection. We aimed to evaluate and summarize the value of the OSNA assay for the diagnosis of SLN metastasis in cytokeratin 19 (CK19)-positive breast cancer. Methods To evaluate the diagnostic value, the sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and area under the curve (AUC) were pooled. The threshold effect, followed by subgroup analysis, was performed to explore the source of heterogeneity. A sensitivity analysis was performed to assess the stability of this meta-analysis model. Fagan plots and likelihood ratio scattergrams were used to explore the potential clinical significance. Results A total of 29 eligible studies, which consisted of 5,331 patients with 10,343 SLNs, were included in this meta-analysis. The pooled sensitivity, specificity, PLR, NLR, and DOR were 0.86 (95% CI: 0.85–0.88), 0.94 (95% CI, 0.94–0.95), 18.00 (95% CI, 13.54–23.92), 0.13 (95% CI, 0.10–0.17), and 138.99 (95% CI, 86.66–222.92), respectively. The AUC was 0.97 (95% CI, 0.95–0.98). Sensitivity analysis showed that four studies had an impact on the pooled results and mainly contributed to the heterogeneity. Fagan's nomogram revealed that the prior probability was 50%, the post-probability positive was 95%, and the post-probability negative was 11%. Discussion Our results suggested that OSNA can predict the occurrence of SLN metastasis in CK19-positive breast cancer. However, more well-designed and multicenter diagnostic tests are needed to validate our results.